Green technologies and firms' market value: a micro-econometric analysis of European firms. (1st April 2020) - Colombelli, Alessandra; Ghisetti, Claudia; Quatraro, Francesco
Abstract: This paper investigates the impact of the generation of green (environmental) technologies on the market value (MV) of a sample of listed companies. The analysis is grounded on the combination of two different theoretical approaches, that is the one focusing on the relationship between MV and innovation and the one pertaining to the economic effects of eco-innovation. Environmental regulation, based on the regulatory push–pull effect, induces firms to cope with more stringent rules through innovation efforts, and this eventually leads to the emergence of new markets for the suppliers of green technologies (GTs). Our main hypothesis is that firms able to generate GTs can be expected to show better stock market performances in this framework, because of the prospects of regulation-driven profitability gains. The empirical analysis has been carried out on a sample of listed firms from France, Germany, Italy, the Netherlands, and the UK observed over the 1985–2011 time span, and it is based on the implementation of the most recent version of the MV equation, corrected for selection bias. Results are consistent with those of previous literature and highlight the positive impact of innovation on MV. When narrowing the focus to firms operating in sectors with a high propensity to generate GTs, we have found that the stringency of the environmental regulatory framework also yields a positive a significant impact, as does the stock of GTs vis-à-vis non-GTs. Moreover, environmental regulatory framework positively moderates the positive effect of the stock of GTs. Lastly, the quality of firms' own knowledge stocks is also found to positively influence firms' MV.